Atmospheric oxidation of C10 14 n-alkanes initiated by Cl atoms: Kinetics and mechanism. (1st February 2020) - Shi, Bo; Wang, Weigang; Zhou, Li; Sun, Zheng; Fan, Cici; Chen, Yan; Zhang, Wenyu; Qiao, Yanyang; Qiao, Yanliu; Ge, Maofa
Abstract: The Cl-initiated photo-oxidation reactions of n-alkanes: C10 C14, were investigated by using Proton-Transfer-Reaction Mass Spectrometry in the smog chamber, and the present work provided the kinetic parameters of the reactions of Cl atoms with C11 14 n-alkanes for the first time. The rate constants (in units of cm 3 molecule −1 s −1 ) were obtained using relative rate method with trans-2-butene, m-xylene and ethylbenzene as references at (298 ± 1)K and 760 Torr were k(n-decane) =(4.82 ± 0.32) × 10 −10, k(n-undecane) =(5.02 ± 0.33) × 10 −10, k(n-dodecane) =(5.12 ± 0.29) × 10 −10, k(n-tridecane) =(5.30 ± 0.30) × 10 −10, k(n-tetradecane) =(5.68 ± 0.34) × 10 −10, respectively. The measured rate constants have also been used to calculate tropospheric lifetimes of these compounds (C10, C11, C12, C13, C14 ), which were 11.5, 11.1, 10.9 10.5 and 9.8 h for each n-alkane. In addition, the gas-phase photooxidation products of the reactions were also measured. Based on the obtained results, the reaction mechanisms of Cl atoms with these five alkanes were proposed. Graphical abstract: Image 1 Highlights: Rate constants for reaction of C11 14 n-alkanes with Cl atoms were firstly obtained. Gas-phase products of C10 14 n-alkanes and Cl atoms were analyzed. The reaction mechanism of the title reactions was deduced.